Efektivitas Penambahan Vitamin E (alfa-Tokoferol) dalam Medium Pencucian Sperma dengan Sentrifugasi terhadap Kualitas Spermatozoa Sapi Brahman - Dasrul Dasrul; Rasmaidar Rasmaidar; Abdul Harris (Jurnal Agripet, 2012)
Effect of vitamin E addition (alfa-tokoferol) into sperm washing medium by centrifuge on the quality of Brahman cattle spermatozoaABSTRACT. The aims of study to determine the effectiveness of the addition of vitamin E in the washing medium by centrifugation on sperm quality Brahman cattle. frozen semen of Brahman cattle, divided into 4 treatment groups addition of vitamin E in the washing medium: 0.0gr/100 ml medium (K0), 0.1gr /100 ml medium (K1); 0.2gr/100 ml medium (K2) and 0.3 g / 100 ml medium (K4), each group was repeated 5 times. Examination of motility, viability and integrity of sperm membrane performed according to WHO standards. The data obtained were analyzed with one-way ANOVA and Duncan test. The average percentage of motility, viability and membrane integrity of spermatozoa in the addition of vitamin E were significantly different (P 0.05) compared to the control. Percentage of motility, viability and membrane integrity of spermatozoa in the group K2 significantly higher (P 0.05) compared with the group K3: K1 and K0. Percentage of motility, viability and sperm capacitation and sperm live on group K3 significantly higher (P 0.05) compared with the K1 and K0. While the percentage motility of spermatozoa in the group K1 higher were not significant (P 0.05) compared with the group K0. The addition of vitamin E in the medium on the process of washing spermatozoa Brahman cattle. The addition of vitamin E 0.2gr/100ml better than vitamin E 0.1gr/100ml and 0.3gr/100ml in maintaining the percentage of motility and live spermatozoa Brahman cattle.